2014
DOI: 10.1088/1751-8113/47/22/225001
|View full text |Cite
|
Sign up to set email alerts
|

Validity conditions of the hydrostatic approach for self-gravitating systems: a microcanonical analysis

Abstract: We consider a system of hard spheres with gravitational interactions in a stationary state described in terms of the microcanonical ensemble. We introduce a set of similar auxiliary systems with increasing sizes and numbers of particles. The masses and radii of the hard spheres of the auxiliary systems are rescaled in such a way that the usual extensive properties are maintained despite the long-range nature of the gravitational interactions, while the mass density and packing fractions are kept fixed. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…The probability of such events is extremely low so that, in practice, the system remains in the metastable phase [8]. 7 Similar phase transitions are obtained if, instead of quantum particles, we consider classical particles and regularize the gravitational potential at short distances [25,[29][30][31] or take into account the finite size of the particles by considering a hard spheres gas [6,23,28,[32][33][34]. Even if the details of the phase transitions depend on the specific form of the small-scale regularization, the phenomenology of these phase transitions is relatively universal as described in [8].…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…The probability of such events is extremely low so that, in practice, the system remains in the metastable phase [8]. 7 Similar phase transitions are obtained if, instead of quantum particles, we consider classical particles and regularize the gravitational potential at short distances [25,[29][30][31] or take into account the finite size of the particles by considering a hard spheres gas [6,23,28,[32][33][34]. Even if the details of the phase transitions depend on the specific form of the small-scale regularization, the phenomenology of these phase transitions is relatively universal as described in [8].…”
Section: Introductionmentioning
confidence: 57%
“…As a result, for µ ≫ 1, the solutions A and B have almost the same temperature (β A ≃ β B ) and the profiles A and B coincide outside of the nucleus (see Figs. [34][35][36]. This is why the branches A and B in the series of equilibria superimpose for µ → +∞ (see Fig.…”
Section: Density Profiles and Rotation Curves Of The Fermionic Kinmentioning
confidence: 99%
“…Figure 7 shows the kurtosis for the distribution of the sum of M subsequent position variables as a function of M for both cases of regularization, with an energy per particle e = −0.7 such that the particles form a compact cluster. For both cases the kurtosis oscillates around the expected value for uncorrelated variables, indicating that the mean field description is still valid with a hard-core part in the potential, although a further study on the validity of the mean field approach for long-range interacting potentials with a short-range divergence is still in need [32]. is drawn for reference.…”
Section: B Hard-core Regularizationmentioning
confidence: 96%
“…It can be shown that the statistical mechanics approach gives exactly the same results as the thermodynamic approach in a proper thermodynamic limit where the number of particles N → +∞ keeping Λ = −ER/GM 2 and η = βGM m/R fixed [101]. We refer to [107][108][109][110] for rigorous mathematical results on this subject.…”
Section: Introductionmentioning
confidence: 98%